The noigandres poets and concrete art (PÓS: Revista do Programa de Pós-graduação em Artes da EBA/UFMG, 2023)
This essay is the first study to examine the relations, in creative practice, in theoretical orientation, and in collaboration and personal contacts, between Brazilian Concrete art and poetry, especially between the “Ruptura” group and the “Noigandres” poets of São Paulo, during the period of 1952-1962.